ZEN-garden: Optimizing energy transition pathways with user-oriented data handling - Jacob Mannhardt; Alissa Ganter; Johannes Burger; Francesco De Marco; Lukas Kunz; Lukas Schmidt-Engelbertz; Paolo Gabrielli; Giovanni Sansavini (SoftwareX)
Welcome to the ZEN-garden: ZEN-garden is an open-source optimization software to model multi-year energy system transition pathways. To support research focused on the transition of sector-coupled energy systems toward net-zero emissions, ZEN-garden is built upon two principles: Optimizing highly complex sector-coupled energy transition pathways and supporting user-friendly data handling through small, flexible, and robust input datasets. ZEN-garden separates the codebase from the input data to allow for very diverse case studies. Lightweight and intuitive input datasets and unit consistency checks reduce user errors and facilitate using ZEN-garden for both novice and experienced energy system modelers.